BRAND IMAGE, KREATIVITAS IKLAN DAN KEPERCAYAAN TERHADAP MINAT BELI KAUM MILENIAL PENGGUNA SHOPEE DI KOTA BATAM - Lussy Putri Satriawan; Asron Saputra (Universitas Muhammadiyah Tangerang, 2023)
This study aims to determine the effect of brand image, advertising creativity and trust on the buying interest of millennial Shopee users in Batam City. This research uses quantitative methods. The population in this study were millennials who had used or transacted through Shopee e-commerce with a sample size of 337 respondents. The sample technique used was purposive sampling using certain criteria to be sampled. The analysis method used in this study is descriptive analysis method, causality test, classical assumption test, multiple linear regression analysis and hypothesis testing. The results showed that Brand Image and Trust had a partial and significant effect on purchase intention while advertising creativity had no partial and significant effect on purchase intention.